Iron oxide reduction by graphite and torrefied biomass analyzed by TG-FTIR for mitigating CO2 emissions - Ubando, Aristotle T.; Chen, Wei-Hsin; Ong, Hwai Chyuan (Elsevier, 2019)
Biomass provides a sustainable source for iron oxide reduction and can replace coal for mitigating CO2 emissions. Torrefied biomass can act as a reducing agent in the iron oxide reduction to metallic iron which is important in chemical-looping combustion for lessening CO2 emissions. This study performs iron oxide reduction by graphite and torrefied biomass via thermogravimetric analysis (TGA), while the evolved gases from the reduction processes are analyzed using a Fourier transform infrared (FTIR) spectrometer. Iron ore reduction by graphite occurs at higher temperatures (>950 °C), whereas iron oxide reduction using the torrefied biomass is more significant for low-to medium-range temperatures with an onset temperature of 300 °C. The reduction extent is recognized from the comparison between theoretical and experimental TGA curves, and validated by the evolved gases. The reduction extent of the 2:1 ratio of hematite-to-torrefied biomass shows a lower onset reduction temperature compared to the 1:1 ratio. The TG-FTIR results confirm the direct reduction of iron oxides by carbon in graphite and torrefied biomass and the release of evolved CO2 instead of CO. A step-wise reduction procedure is observed which is triggered by the evolved gases released from torrefied biomass devolatilization at 370 °C. © 2019 Elsevier Ltd